Karyono POLA-POLA GERAK PADA TOPENG BARONGAN KERTAS SEBAGAI INOVASI PENGEMBANGAN TRADISI KERAKYATAN - Karyono; Tubagus Mulyadi (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
Barongan Blora is one of the communal arts that developed in the Blora, Rembang and Grobogan areas.Barongan dish was originally a spiritual form of its presence, not paying attention to the aesthetic elementsmore focused on its function. Barongan movement patterns cannot be separated from the Barong mask whichhas been made from wood which is the shape of a large mask. This greatly affects the patterns of movementin the Barong dance.The innovation of the Barongan mask as a form of developing a populist tradition has analternative in making masks made from paper. This is done to get the possibility of movement patterns relatedto the development of innovation in the Barong populist arts tradition. The creative engineering effort of theBarongan mask by utilizing waste paper becomes an alternative to enrich the work of dance moves related tothe lighter mask properties as a large mask performance. Replacing wood media with paper in mask making.With the hope of facilitating the game techniques in accordance with the character of Barong and silat movementsas if kanuragan.The purpose of this study is to look for basic concepts about Barongan movementpatterns that are technically related to paper mask media. The research method used is rise up by practice,the artistic method, the creation of art based on research.The results of the study showed that the movementpatterns were worked on as the basis for developing the Barongan Kertas mask dance. Research outputstargeted at this study are; Intellectual Property Rights and National Journal.